The Effect of Reflective Journaling on Writing Skills of English As a Foreign Language Students: A Quasi-Experimental Study - Nur Aisyah Amalia; Abdul Syahid; Akhmad Ali Mirza (Journal on Education, 2024)
Reflective journaling defined as a development-oriented assessment in which contributes students to reach potential capabilities through analyzing their learning process. The students engaged in reflection of their learning process through reflective journal writing. The present study focused to investigate the effect of reflective journaling on writing skills of English as A Foreign Language (EFL) students. Two classes of twelfth grade students in a state Islamic school were involved in the study. The participants were assigned to two groups (experimental and control) and involved in writing test. Experimental group was provided by reflective journal template adapted from Gibb’s Reflective Cycle. The analysis was significant with p value was 0.024 in which less than critical value 0.05. The results indicated that students who used reflective journal significantly different compared to those do not use it.